Perancangan Sistem Informasi Alumni Menggunakan Pendekatan OOP untuk Meningkatkan Konektivitas Lulusan dan Efisiensi Administrasi Prodi Teknologi Rekayasa Perangkat Lunak - Alma’ Abdhillah; Raden Mas Galih Pradityo; Muhammad Ramadhan; Dika Aprilio Wibowo; Aditya Wicaksono; Endang Purnama Giri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The management of alumni data for the Software Engineering Technology (SET) Study Program is currently facing challenges, including dispersed data, difficulty in updating, and administrative inefficiencies. This study aims to design a structured and centralized web-based Alumni Information System. The method used is Object-Oriented Analysis and Design (OOAD), which includes literature review, requirements identification, UML modeling (use case, activity, class, sequence diagrams), and interface design. The design results indicate that the system provides nine main functional features, which address the data management problems. The Object Oriented Programming (OOP) approach is applied to produce a system architecture that is modular, maintainable, and scalable. The designed system is estimated to increase administrative process efficiency by more than 90%, instantly reducing data search and verification time. Overall, this design is expected to enhance data accuracy, alumni connectivity, and operational efficiency of the study program.